PENGARUH KONDISI SOSIAL EKONOMI YANG MENDORONG PENINGKATAN PRODUKTIVITAS USAHATANI CABAI MERAH DI MASA PANDEMI - Pankrasius Purnama Umatron; Cakti Indra Gunawan; Ery Yusnita Arvianti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine differences in the productivity of red chili farming before and after the pandemic. The researcher used probability sampling technique with 201 red chili farmers as the sampling population with a data collection error rate of 0,10% in order to obtain 66 research samples. The parameter of analysis is productivity before and after the pandemic using the paired sample t-test. The results showed that the significance value was obtained (0,004<0,05), then H1 was accepted and H0 was rejected. This means that there is a significant difference between the productivity of red chili farming before and after the pandemic.